Two new species of bent toed geckos, Cyrtodactylus Gray, 1827 (Squamata: Gekkonidae) from Northeast India with comments on name-bearing types from the region - Agarwal, Ishan; Mahony, Stephen; Giri, Varad B.; Chaitanya, R.; Bauer, Aaron M. (Zootaxa, 2018)
Two new species of the genus Cyrtodactylus are described based on collections from Northeast India, and descriptions and diagnoses of previously described species and synonyms from the region are provided. One of the new species from lowland habitats in Tripura is medium sized, with a continuous series of precloacal pores, and is allied to C. ayeyarwadyensis from Myanmar; while the other new species from West Bengal is smaller, with both femoral and precloacal pores, and is related to C. gubernatoris from West Bengal and Sikkim. We designate a lectotype for Cyrtodactylus khasiensis and recognize the C. khasiensis synonym Gymnodactylus himalayicus as a valid species of Cyrtodactylus based on morphological evidence, and suggest the recognition of the last remaining subspecies of C. khasiensis, C. k. cayuensis, as a valid species based on geography and morphology. The stabilization of the taxa Cyrtodactylus khasiensis and C. gubernatoris with a limited subset of characters and specific distributional data, as well as the elevation of Cyrtodactylus himalayicus comb. nov. from synonymy, will allow the descriptions of many more Cyrtodactylus species from the region.